(untitled) (Western European Journal of Medicine and Medical Science, 2024)
The introduction of tyrosine kinase inhibitors into clinical practice has significantly improved treatment outcomes for patients with radioiodine-refractory differentiated thyroid cancer (RR-DTC). Lenvatinib is recommended as a first-line drug for this category of patients